A High-Density Human Mitochondrial Proximity Interaction Network - Hana Antonicka (2020)
© 2020 Elsevier Inc. We used BioID, a proximity-dependent biotinylation assay with 100 mitochondrial baits from all mitochondrial sub-compartments, to create a high-resolution human mitochondrial proximity interaction network. We identified 1,465 proteins, producing 15,626 unique high-confidence proximity interactions. Of these, 528 proteins were previously annotated as mitochondrial, nearly half of the mitochondrial proteome defined by Mitocarta 2.0. Bait-bait analysis showed a clear separation of mitochondrial compartments, and correlation analysis among preys across all baits allowed us to identify functional clusters involved in diverse mitochondrial functions and to assign uncharacterized proteins to specific modules. We demonstrate that this analysis can assign isoforms of the same mitochondrial protein to different mitochondrial sub-compartments and show that some proteins may have multiple cellular locations. Outer membrane baits showed specific proximity interactions with cytosolic proteins and proteins in other organellar membranes, suggesting specialization of proteins responsible for contact site formation between mitochondria and individual organelles.